Формування позитивного туристичного іміджу рідного краю (на прикладі Путиль-ської, Усть-Путильської, Селятинської ОТГ Чернівецької області України) для по-пуляризації його на туристичному ринку - Круль, Галина; Тонієвич, Тетяна (The XIII International Scientific and Practical Conference "Modern ways of development of science and the latest theorie, Madrid, Spain, 2023)
The paper examines the formation of the tourist image of Putylska, Ust-Putilska, and Selyatyn OTG for popularization on the tourist market of Ukraine. The essence of the concept of "image", "tourist image" is revealed and the factors of its formation are determined. The recreational and touristic potential of the region was studied. The strengths and weaknesses, opportunities and threats of the research region are analyzed. The prospects of the attractiveness of the tour among tourists were analyzed, the integration of the region into the developed tour was substantiated. A number of measures to popularize the research region are given.
Keywords: імідж; туристичний імідж; іміджеві чинники; туристичний потенціал; етнокультурна спадщина; тур вихідного дня